RELASI POLITIK DENGAN IMPLEMENTASI PENDIDIKAN ISLAM - Ahmad, Ahmad (Jurnal Al-Ulum : Jurnal Pemikiran dan Penelitian Ke-Islaman, 2017)
Efforts to transform humanity with knowledge of attitudes and behaviors that conform to Islamic values or ideology can only be done with education. Thus, Islamic education is a process to bring humanity closer to the level of its perfection and to develop the level of its ability which is guided by Islamic ideology and aqidah. As the goal of Islamic education is to create human beings who are Islamic and soulful in accordance with the spirit and breath of Islam. Methodology that is not oriented towards the achievement of these goals will certainly be avoided, so that Islamic education is not merely transfer of knowledge, but pay attention to whether the given science can change attitudes and behavior or not. Within this framework, intensive monitoring by all levels of society, including the government on the patterns and behavior of learners, to what extent they are bound by the Islamic conception of life and values.